A practical microreactor for electrochemistry in flow - Watts, Kevin; Gattrell, William; Wirth, Thomas (Beilstein Journal of Organic Chemistry, 2011)
A microreactor for electrochemical synthesis has been designed and fabricated. It has been shown that different reactions can be carried out successfully using simple protocols.
Keywords: diaryliodonium compounds; electrochemistry; flow chemistry; microreactor